Karl marx and world literature - Prawer, S.S. (London, 2011)
(3z(BVery few men,(3y (Bsaid Bakunin, (3z(Bhave read as much, and, it may be added, have read as intelligently, as M. Marx.(3y (BS. S. Prawer$1 (Bs highly influential work explores how the world of imaginative literature$1 (Bpoems, novels, plays$1 (Binfused and shaped Marx$1 (Bs writings, from his unpublished correspondence, to his pamphlets and major works. In exploring Marx$1 (Bs use of literary texts, from Aeschylus to Balzac, and the central role of art and literature in the development of his critical vision, Karl Marx and World Literature is a forensic masterpiece of critical analysis.s
Keywords: Marxism